Epidemiological insights into severe hepatitis in pediatric inpatients - Fuping Guo; Xudong Ma; Qijun Shan; Yuelun Zhang; Sifa Gao; Jieqin Chen; Yujie Chen; Dawei Liu; Taisheng Li; Feng Zhang; Xiang Zhou (iScience)
Summary: There is limited statistical data on severe hepatitis among hospitalized children in China at a national level. This nationwide study analyzed data from 34,410 children hospitalized for severe hepatitis in mainland China from 2016 to 2022. The overall in-hospital mortality rate was 6.1%. Viral hepatitis accounted for 14.9% of cases, with hepatitis B being the most prevalent. Indeterminate etiology, present in 79.0% of cases, was an independent risk factor for mortality. Findings emphasize the need for enhanced diagnostic methods and targeted interventions for children with severe hepatitis of unknown cause and suggest focused hepatitis B monitoring in older children to improve outcomes. Establishing a dedicated surveillance system is crucial for improving the prognosis of children at high risk for in-hospital mortality due to severe hepatitis.